2018
DOI: 10.1002/jmv.25271
|View full text |Cite
|
Sign up to set email alerts
|

Application strategies of serum HBV DNA detection in HBV infection patients: A retrospective study of 5611 specimens

Abstract: The detection of hepatitis B virus (HBV) DNA plays a critical role in determining the level of viral replication in HBV-infected patients. However, how to select appropriate HBV DNA detection method, low-sensitivity (ls) and hypersensitivity (hs) remains unclear. In this study, hepatitis B surface antigen (HBsAg), hepatitis B e-antigen (HBeAg), alanine transaminase (ALT), aspartate transaminase (AST), and hs HBV DNA titers in serum of 5611 cases with suspected HBV infection were reviewed. Besides, the dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…OPN may increase the rate of virus replication and assembly [19,30]. Serum HBV DNA quantified by realtime fluorescent quantitative PCR is a key factor for determining the level of viral replication in the various phases of HBV infection [31]. But, in this study, viral load was not found to be associated with the concentrations of serum OPN, a finding is consistent with other studies [16].…”
Section: The Association Of Viral Factors With the Serum Concentrations Of Opnsupporting
confidence: 89%
“…OPN may increase the rate of virus replication and assembly [19,30]. Serum HBV DNA quantified by realtime fluorescent quantitative PCR is a key factor for determining the level of viral replication in the various phases of HBV infection [31]. But, in this study, viral load was not found to be associated with the concentrations of serum OPN, a finding is consistent with other studies [16].…”
Section: The Association Of Viral Factors With the Serum Concentrations Of Opnsupporting
confidence: 89%
“…Hypoviremia also exists in patients with chronic HBV infection, which means that the hepatitis B DNA load in plasma is lower than 2000 IU/mL (fluctuation range is 20 ~ 2000 IU/mL) if HBV persists or can be detected occasionally (8). Ordinary PCR reagents cannot detect this situation; only highly sensitive PCR reagents can do so (28). In the past, it was believed that the low HBV DNA load had little impact on the progress and harm of the disease.…”
Section: Untreated Patients With Hypoviremia Also Face the Risk Of Di...mentioning
confidence: 99%